Atomically Thin Mesoporous Co3O4 Layers Strongly Coupled with N‐rGO Nanosheets as High‐Performance Bifunctional Catalysts for 1D Knittable Zinc–Air Batteries. Issue 4 (6th December 2017) - Li, Yingbo; Zhong, Cheng; Liu, Jie; Zeng, Xiaoqiao; Qu, Shengxiang; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Lu, Jun
Abstract: Under development for next‐generation wearable electronics are flexible, knittable, and wearable energy‐storage devices with high energy density that can be integrated into textiles. Herein, knittable fiber‐shaped zinc–air batteries with high volumetric energy density (36.1 mWh cm −3 ) are fabricated via a facile and continuous method with low‐cost materials. Furthermore, a high‐yield method is developed to prepare the key component of the fiber‐shaped zinc–air battery, i.e., a bifunctional catalyst composed of atomically thin layer‐by‐layer mesoporous Co3 O4 /nitrogen‐doped reduced graphene oxide (N‐rGO) nanosheets. Benefiting from the high surface area, mesoporous structure, and strong synergetic effect between the Co3 O4 and N‐rGO nanosheets, the bifunctional catalyst exhibits high activity and superior durability for oxygen reduction and evolution reactions. Compared to a fiber‐shaped zinc–air battery using state‐of‐the‐art Pt/C + RuO2 catalysts, the battery based on these Co3 O4 /N‐rGO nanosheets demonstrates enhanced and stable electrochemical performance, even under severe deformation. Such batteries, for the first time, can be successfully knitted into clothes without short circuits under external forces and can power various electronic devices and even charge a cellphone. Abstract : Knittable fiber‐shaped zinc–air batteries based on atomically thin mesoporous Co3 O4 layers strongly coupled with nitrogen‐doped reduced graphene oxide nanosheets as bifunctional catalysts of the air electrodes are developed and can be fabricated by a quick, facile, and continuous method. These high‐energy‐density batteries can be knitted into clothes and used as the power supply for wearable electronic devices.